Numerical analysis on the sloshing of free oil liquid surface under the variable conditions of vehicle. (February 2019) - He, Ren; Zhang, Enhui; Fan, Baowei
Oil liquid sloshing is the sloshing of free oil liquid surface in the fuel tank filled partially. The variable conditions of vehicle mainly include braking, acceleration, and deceleration. It is verified that the simulation method is reliable by the test. In this study, numerical simulations are carried out to study the sloshing of free oil liquid surface under the variable conditions of vehicle, and the key factors influencing variable conditions are acceleration value of oil liquid sloshing, the lasted time of acceleration, and the amount of fuel filled. The numerical results of oil liquid sloshing under variable conditions are compared. The results show that the influence of the amount of fuel filled on oil liquid sloshing and evaporative emission is greater than that of the other two factors under the same working conditions. The time-area values of acceleration lasted time of 1 s are bigger than that of 4 s and the time-area values of 50% fuel filled are bigger than that of 25% fuel filled during the same time of sloshing, and the change law of evaporative emission is the same as that of time-area values.